Examination of the Porosity in Reactive Air Brazed Joints by Ultrasonic Testing. Issue 12 (20th May 2014) - Tillmann, Wolfgang; Sievers, Norman; Pfeiffer, Jan; Wojarski, Lukas; Zielke, Reiner; Poenicke, Andreas; Schilm, Jochen; Kuhn, Bernd; Beck, Tilmann
<x xml:space="preserve">Abstract</x> Reactive air brazing (RAB) has been developed as a method to join ceramics and steel, using CuO as a reactive agent that interacts with the surface of the ceramic, enabling a wetting by the molten filler metal. A major benefit of this method is the fact that the joining process can be carried out in an ambient atmosphere, in contrast to active brazing processes, which need to be performed in a vacuum furnace. In the past, several investigations were conducted to improve the mechanical bonding properties for both methods. A sealed gas‐tightness is also important for innovative applications such as solid oxide fuel cells. In this regard, the reduction of porosity, which is necessary in order to achieve reproducible joints with a long lifetime, presents a challenge. Therefore, it is necessary to conduct fundamental analyses of the driving forces and mechanisms of the formation of voids in the interfacial area to guarantee a reliable joint quality. In this study, the authors used an ultrasonic testing method in the realm of the immersion technique to evaluate the porosity in brazements produced with varying process parameters. A major goal was to assess the influence of the cooling stage on the pore formation. The advantage of this non‐destructive method is the possibility to scan the entire joint area using just one scan. The investigations were flanked by SEM analyses on different cross‐sections.